1966
DOI: 10.2307/3895724
|View full text |Cite
|
Sign up to set email alerts
|

Range Reseeding Success on the Tonto National Forest, Arizona

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1972
1972
1987
1987

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The results with juniper slash mulching in this study generally agree with those of the limited studies done previously (Judd 1948;…”
Section: Mulchingsupporting
confidence: 92%
See 1 more Smart Citation
“…The results with juniper slash mulching in this study generally agree with those of the limited studies done previously (Judd 1948;…”
Section: Mulchingsupporting
confidence: 92%
“…Limited work done on juniper ranges in the 1940's and 1950's indicated that natural mulches seemed to improve establishment and maintenance of grass stands (Judd 1948;Judd 1966;Lavin unpublished data). However, the practice of range mulching was considered too expensive, and no followup studies were done at that time.…”
mentioning
confidence: 99%
“…The plantings used were all seeded and evaluated in the same way. The results of other species adaptation trials in the southwestern pinyon-juniper have been reported by Judd (1966), and Judd and Judd (1976) for Arizona; and Merkel and Herbel (1973) and for New Mexico.…”
Section: Juniper Effects On Reseedingmentioning
confidence: 64%
“…Natural mulching materials improved seeding results in early southwestern pinyon-juniper seeding trials (Judd 1948(Judd , 1966 but the practice was felt to be too expensive and was not developed further. Since then, many different materials such as straw, litter, cinders, gravel, asphalt, and plastic films have been tried (Springfield 1972;Lavin and others 1981).…”
Section: Planting Methodsmentioning
confidence: 99%
See 1 more Smart Citation